Nuclear Receptor PXR Confers Irradiation Resistance by Promoting DNA Damage Response Through Stabilization of ATF3 - Niu, Xiaxia; Cui, Hongmei; Gu, Xinsheng; Wu, Ting; Sun, Min; Zhou, Changlong; Ma, Mei (Frontiers in Oncology, 2022)
Low response rate to radiotherapy remains a problem for liver and colorectal cancer patients due to inappropriate DNA damage response in tumors. Here we report that Pregnane X receptor (PXR) contributed to irradiation (IR)-resistance by promoting activating transcription factor 3 (ATF3)-mediated ATM activation. PXR stabilized ATF3 protein by blocking its ubiquitination. PXR-ATF3 interaction is required for regulating ATF3 as one mutant of lysine (K) 42R of ATF3 lost binding with PXR and abolished PXR-reduced ubiquitination of ATF3. On the other hand, threonine (T) 432A of PXR lost binding with ATF3, and further compromised ATM activation. Moreover, the PXR-ATF3 interaction increases ATF3 stabilization through disrupting ATF3-MDM2 interaction and negatively regulating MDM2 protein expression. PXR enhanced MDM2 auto-ubiquitination and shortened its half-life, therefore, compromised the MDM2-mediated degradation of ATF3 protein. Structurally, both ATF3 and PXR binds to the RING domain of MDM2, and on the other hand, MDM2 binds with PXR on the DNA binding domain (DBD), which contains Zinc-finger sequence. Zinc-finger sequence is well known for nuclear receptor peroxisome proliferator-activated receptor-γ (PPARγ) playing E3 ligase activity to degrade nuclear factor κB (NFκB)/p65. However, whether zinc-RING sequence grants E3 ligase activity to PXR remains elusive. Taken together, these results provide a novel mechanism that PXR contributed to IR-resistance by promoting ATF3-mediated ATM activation through stabilization of ATF3. Our result suggested that targeting PXR may sensitize liver and colon cancer cells to irradiation therapy.